METHOD FOR DETERMINATION OF NUMERICAL FRICTION WORK VALUE AS INTEGRATED PARAMETER AT ONBOARD DIAGNOSING OF BRAKE LINING WEAR - Y. D. Karpievich (Наука и техника)
A method for determination of numerical friction work value corresponding to maximum permissible wear of a brake lining has been developed in the paper.